2020
DOI: 10.3389/fnins.2020.00063
|View full text |Cite
|
Sign up to set email alerts
|

Cynomolgus Monkeys With Spontaneous Type-2-Diabetes-Mellitus-Like Pathology Develop Alpha-Synuclein Alterations Reminiscent of Prodromal Parkinson’s Disease and Related Diseases

Abstract: Available evidence suggests that diabetes mellitus (DM) is a non-genetic risk factor for Parkinson's disease (PD). PD and DM have shared similarities in pathogenetic mechanisms, including age, environmental factors, inflammatory reaction, and protein aggregation, etc. α-Synuclein is the primary protein component in the protein inclusions in PD, while islet amyloid polypeptide (IAPP) aggregates to form amyloid structures in β cells in type 2 diabetes mellitus (T2DM). Pancreatic and cerebral functions, pancreas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 67 publications
(74 reference statements)
1
29
2
Order By: Relevance
“…Recently, pathological pS129-positive α-syn deposits were found in the pancreatic beta cells of 93% of subjects with PD, in 68% of subjects with T2D following neuropathological examination and in 17% of control subjects (Martinez-Valbuena et al, 2018). Further, increased accumulation, aggregation, and phosphorylation of α-syn was observed in the pancreatic islets of non-human primate models of spontaneous T2D (Sun et al, 2020). Serum α-syn levels were also inversely correlated with insulin resistance indicators such as body mass index, homeostatic model assessment for IR (HOMA-IR) and immunoreactive insulin (Rodriguez-Araujo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pathological pS129-positive α-syn deposits were found in the pancreatic beta cells of 93% of subjects with PD, in 68% of subjects with T2D following neuropathological examination and in 17% of control subjects (Martinez-Valbuena et al, 2018). Further, increased accumulation, aggregation, and phosphorylation of α-syn was observed in the pancreatic islets of non-human primate models of spontaneous T2D (Sun et al, 2020). Serum α-syn levels were also inversely correlated with insulin resistance indicators such as body mass index, homeostatic model assessment for IR (HOMA-IR) and immunoreactive insulin (Rodriguez-Araujo et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In order to validate the effectiveness of our high-order FC network, we compare it with C-FCN and LoD-FCN. Specifically, the comparison method utilizes the C-FCN matrix and extracts statistical features based on central moment (i.e., CM-FCN) ( Zhao et al, 2020 ) and root-mean-square (RMS) ( Chen et al, 2017 ) from LoD-FCN as original features, and then perform feature selection for SVM classification. The best classification performances of comparison methods are summarized in Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…FC network has been of great importance for discovering the functional organization of human brain and searching for the biomarkers of the neuropsychiatric disorders, such as Alzheimer’s disease ( Chen et al, 2017 ; Hao et al, 2017 ) and autism spectrum disorder (ASD) ( Zhao et al, 2018 ; Wee, Yap & Shen, 2016 ). Currently, researchers have proposed various FC network modeling methods for ASD assisted diagnosis ( Liu & Huang, 2020 ; Zhao et al, 2020 ; Zhao et al, 2021 ). For example, Liu & Huang (2020) estimated the severity of ASD by multivariate model analysis, and they found that some FCs suffer from abnormal alterations in ASD patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations